1999
DOI: 10.1007/s004210050487
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum levels of 1,25-(OH) 2 vitamin D during 1 year of sunlight deprivation in the Antarctic

Abstract: French Antarctic territories harbor bases that are devoted to scientific and technical work. Living and working conditions during 1-year sojourns in such an environment are quite acceptable, but the confinement and the drop in ultraviolet B radiation exposure during winter months raise the problem of preservation of normal vitamin D status. Seasonal variations in 25-hydroxyvitamin D [25(OH)D] levels have been well documented, but the effect of sunshine deprivation on 1,25 dihydroxyvitamin D [1,25(OH)2D] levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…As in other studies conducted in Antarctica, bone-specific alkaline phosphatase increased over time, which indicated that bone formation may have increased (23,24). It is possible that 1,25-dihydroxyvitamin D and calcium increased in response to a feedback mechanism to maintain available calcium when bone remodeling increased, as evidenced by the increase in bone-specific alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 50%
“…As in other studies conducted in Antarctica, bone-specific alkaline phosphatase increased over time, which indicated that bone formation may have increased (23,24). It is possible that 1,25-dihydroxyvitamin D and calcium increased in response to a feedback mechanism to maintain available calcium when bone remodeling increased, as evidenced by the increase in bone-specific alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 50%
“…Furthermore, a temporary 1-y sunlight deprivation under Antarctic conditions resulted in a significant decrease of 25(OH)D and 1,25(OH) 2 D levels in 15 healthy adult men, with the lowest levels being observed after 10 mo from departure from southern latitudes (35). This probably indicates that serum 1,25(OH) 2 D may be affected by the seasonal variation of 25(OH)D caused by variation in solar UV irradiance.…”
Section: Discussionmentioning
confidence: 96%
“…Depending on the latitude, months of complete darkness during the Antarctic winter alternate with months of 24-hrs bright daylight in the Antarctic summer [ 9 ]. This has particular consequences on vitamin D homeostasis for humans residing there [ 10 12 ]. Germany currently operates the year-long inhabited research station Neumayer III, which was inaugurated in February 2009; it replaced the previous station Neumayer II, which operated from 1992 to 2009, and which had to be abandoned because its structural integrity could no longer be maintained, as it was located underground within ice [ 13 ].…”
Section: Introductionmentioning
confidence: 99%